2017
DOI: 10.1016/j.lindif.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of genetic and environmental factors on writing development

Abstract: Researchers have identified sources of individual differences in writing across beginning and developing writers. The aim of the present study was to further clarify the sources of this variability by investigating the extent to which there are differences in genetic and environmental factors underlying the associations between lexical diversity, syntactic knowledge, and semantic cohesion knowledge in relation to writing. Differences were examined across two developmental phases of writing: beginning (i.e., el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Caregivers mailed the writing sample and reading vocabulary test back to the research team along with the signed consent and other questionnaire materials. Despite potential limitations of parent-obtained written samples, protocols obtained by mail from parents have been used in other studies where the measures do not require formal training to administer (Buss & Plomin, 2014; Erbeli, Hart, Kim, & Taylor, 2017). All the data were entered into FileMaker using a double-entry procedure at the item level, with programmed calculations used to create total scores.…”
Section: Methodsmentioning
confidence: 99%
“…Caregivers mailed the writing sample and reading vocabulary test back to the research team along with the signed consent and other questionnaire materials. Despite potential limitations of parent-obtained written samples, protocols obtained by mail from parents have been used in other studies where the measures do not require formal training to administer (Buss & Plomin, 2014; Erbeli, Hart, Kim, & Taylor, 2017). All the data were entered into FileMaker using a double-entry procedure at the item level, with programmed calculations used to create total scores.…”
Section: Methodsmentioning
confidence: 99%
“…Isani and Virk (2005) posited that the quality of research is directly and indirectly related to the quality of the facilities available in the universities, lecturers, supervision of research and research courses. The study of Erbeli, Hart, Kim, and Taylor (2017) indicates that environmental factors contribute to individuals' differences in writing.…”
Section: Introductionmentioning
confidence: 99%
“…We have hypothesised that the opportunity for reading exposure and practice is influenced by socio‐demographic factors, and this might, in turn, influence the cognitive capabilities and resources students apply to writing goals. In fact, previous research has shown that individual differences that owe to students' unique experiences are particularly prominent in developing writers in the middle school grades as opposed to beginning writers in elementary school (Erbeli et al, 2017).…”
mentioning
confidence: 99%